INVESTIGATION OF BIOGAS PRODUCTION POTENTIAL AND ADAPTATION TO CATTLE MANURE OF ANAEROBIC FLOCULAR SLUDGE SEED - Tufaner, Fatih; Avsar, Yasar (YILDIZ TECHNICAL UNIV, 2016)
In this study, investigation of biogas production potential and adaption to cattle manure (CM) of flocular sludge seed that was supplied from the wastewater treatment plant digester. The study was carried out with five laboratory scale anaerobic reactors and two bottles of 6.15 L and 1.5 L capacity, respectively. According to the results of the study, adaptation to CM of sludge seed has been realized within a short time such as 3-5 days. It was obtained that biogas production of sludge seed of 3 L was 7 L as a cumulative in 31 days. During this process, an average of about 17 L biogas production has been observed to the volume of the reactors at 6.15 L. Methane production is obtained about 0.35 L CH4/g CODremoval. According to these data, flocular sludge seed was found to be a suitable seed for the system which established for the purpose of anaerobic digestion of CM.
Keywords: Anaerobic digestion; cattle manure; flocular sludge seed; biogas production; PHASE-SEPARATION; SUBSTRATE; DIGESTION; GLUCOSE; Engineering